2019
DOI: 10.1021/acschemneuro.9b00547
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Flavonoid Naringenin Elicits Analgesia through Inhibition of NaV1.8 Voltage-Gated Sodium Channels

Abstract: Naringenin (2S)-5,7-dihydroxy-2-(4-hydroxyphenyl)-3,4-dihydro-2H-1-benzopyran-4-one is a natural flavonoid found in fruits from the citrus family. Because (2S)-naringenin is known to racemize, its bioactivity might be related to one or both enantiomers. Computational studies predicted that (2R)-naringenin may act on voltage-gated ion channels, particularly the N-type calcium channel (CaV2.2) and the NaV1.7 sodium channelboth of which are key for pain signaling. Here we set out to identify the possible mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 79 publications
4
26
1
Order By: Relevance
“…Naringenin, a flavonoid present in sweet oranges and grapefruit, was recently found to improve glucose and lipid homeostasis and mitigate adipose tissue inflammation in rodents and humans [ 27 , [38] , [39] , [40] ]. Naringenin has been shown to interact with voltage-gated ion channels and potentially block VGCCs, including Cav3.2 [ [41] , [42] , [43] ]. We speculated that Cav3.2 expressed by Vgat ARH neurons partially mediates the beneficial metabolic effects of naringenin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naringenin, a flavonoid present in sweet oranges and grapefruit, was recently found to improve glucose and lipid homeostasis and mitigate adipose tissue inflammation in rodents and humans [ 27 , [38] , [39] , [40] ]. Naringenin has been shown to interact with voltage-gated ion channels and potentially block VGCCs, including Cav3.2 [ [41] , [42] , [43] ]. We speculated that Cav3.2 expressed by Vgat ARH neurons partially mediates the beneficial metabolic effects of naringenin.…”
Section: Resultsmentioning
confidence: 99%
“…However, the underlying mechanism in which naringenin modulates energy homeostasis is largely unknown. Recently, naringenin has been found to enter blood–brain barrier (BBB) [ 97 ] and acts as a potential blocker for VGCCs, including Cav3.2 [ [41] , [42] , [43] ], indicating a possible central mechanism through Cav3.2. In our ex vivo brain slice recording study, we found that naringenin decreases the firing activity of Vgat ARH neurons by inhibiting Cav3.2-mediated calcium currents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, naringenin induces analgesia by blocking TRPM3 and activating TRPM8 [64], which might contribute to its analgesic effect. Naringenin also blocks sodium influx in rat DRG neurons by selecting inhibiting Nav1.8 (and not Nav1.7 or Nav1.9) [65]. Collectively, naringenin targets different channels expressed by neurons and immune cell signaling pathways (decreases NFkB activation and stimulates Nrf2) to reduce pain and inflammation.…”
Section: Flavanonesmentioning
confidence: 97%
“…(B) Ion channels expressed by neurons that are targeted by Vitexin, Quercetin, and Naringenin to reduce pain. Vitexin: TRPV1 [38], Quercetin: TRPV1 [63], and Naringenin: TRPV1 [58], TRPA1 [58], TRPM3 [64], Nav 1.8 [65], and TRPM8 [64]. In panel (A), ROS and inflammatory stimuli that activate specific receptors trigger intracellular signaling that will result in pain and inflammation.…”
Section: Pre-clinical Evidence Of Flavonoids For Pain Controlmentioning
confidence: 99%
“…However, specific analgesics for managing chronic pain are an unmet clinic need [1][2][3][4][5]. Voltage-gated sodium ion channels subtype 1.7 (Na v 1.7) and 1.8 (Na v 1.8) have been proven as promising targets for the discovery of new drugs to treat chronic pain and numerous small-molecule inhibitors targeting Na v 1.7 and Na v 1.8 that have been developed in preclinical or clinical studies in recent years [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%